Percepções e entendimentos dos educandos acerca da construção dos saberes a partir da disciplina de ensino religioso no município de João Pessoa - Lelis, Daniel Marcos Gomes de (2023)
This thesis deals with the reflection on the perceptions and understandings of students from the municipal network of João Pessoa, especially regarding the construction of knowledge from the discipline of Religious Education (RE), but in order to obtain the desired results whose generating theme: Perceptions and Understandings of students about the construction of knowledge from the discipline of Religious Education in the city of João Pessoa, as a general objective, it tried to identify the importance of RE from the perception and understanding of knowledge in the light of students. Of the final years, that is, the 8th and 9th years. Concomitant, the specific objectives, to subsidize the processes about the perceptions and understandings, it was about: a) to investigate from the historical processes the contributions of the ER about the construction of the knowledge of the students (as) in the city of João Pessoa-PB; b) identify the contributions of the RE in the redefinition of the meaning of the students' lives. c) Analyze the (in) visible processes in the consolidation of the knowledge necessary for the students' cognitive practice. Thus, the first chapter contributed to the analysis of the theoretical foundations regarding the fundamentals that structured the history and, the defense of the curricular component, that is, the RE, as an area of knowledge, thus, for better sharpness in this process of understanding about the bases that structure the knowledge arising from the RE, the introductory chapter deals with the discussions which legitimize the fruitful contribution that the RE has given in the teaching-learning process of the students, whether in the intellectual, formative, cultural, ethical, moral and religious, in a perspective of teaching advocated by the sciences of religions and current legislation, especially in its Art. 33, of the LDB. Also, still in the aforementioned chapter, it was the RE contributed by the sciences of religions, which gives it the legitimate character of scientificity. The second chapter focused on the guiding reflections of the historical models of education, since guiding the model of education in the light of the RE, without fail, it is necessary to rescue the history. In this perspective, the correlation between education and religiosity is notorious. The third chapter outlined about the guiding methodological principles of the thesis, therefore, phenomenological qualitative research was adopted. The fourth chapter, dealt with the transcription and analysis of the interviews and, finally, the fifth chapter, presents us with the final considerations, in the light of the perceptions and understanding of the students about the construction of the knowledge acquired from the teaching classes religious. Finally, it is concluded that, in contribution to the Graduation and Post-Graduation programs in Sciences of Religions and, to the Basic Education of João Pessoa, the present thesis obtained as a construct of its originality, the conviction that the students, from the final years of elementary school, lived and live their experiences in the light of ER are daily building and re-signifying existential knowledge, such as: Respect for personal and collective life, valuing differences, re-signifying existential meanings, overcoming prejudices, practicing religious tolerance, the culture of peace; thus giving new meaning to family values, dialogue, respect for identity, for life (human, animal, plant...); seeing the world from a perspective of sense and meaning. In view of a humanized, fair and fraternal formation. In addition, as a result of all significant learning, it is concluded that the students of the municipal network of João Pessoa allowed themselves in their learning processes to: know how to be, know how to live together, know how to reframe, know how to identify, know how to perceive themselves, know how to feel yourself, knowing how to accept yourself, knowing how to love and be loved, knowing how to see the world in a perspective of value, is knowing how to be- in-the-other-with-another-for-another.|